Finite locally resonant Metafoundations for the seismic protection of fuel storage tanks. (8th November 2018) - Basone, Francesco; Wenzel, Moritz; Bursi, Oreste S.; Fossetti, Marinella
Summary: This paper introduces a novel seismic isolation system based on metamaterial concepts for the reduction of ground motion‐induced vibrations in fuel storage tanks. In recent years, the advance of seismic metamaterials has led to various new concepts for the attenuation of seismic waves. Of particular interest for the present work is the concept of locally resonant materials, which are able to attenuate seismic waves at wavelengths much greater than the dimensions of their unit cells. Based on this concept, we propose a finite locally resonant Metafoundation, the so‐called Metafoundation, which is able to shield fuel storage tanks from earthquakes. To crystallize the ideas, the Metafoundation is designed according to the Italian standards with conservatism and optimized under the consideration of its interaction with both superstructure and ground. To accomplish this, we developed two optimization procedures that are able to compute the response of the coupled foundation‐tank system subjected to site‐specific ground motion spectra. They are carried out in the frequency domain, and both the optimal damping and the frequency parameters of the Metafoundation‐embedded resonators are evaluated. As case studies for the superstructure, we consider one slender and one broad tank characterized by different geometries and eigenproperties. Furthermore, the expected site‐specific ground motion is taken into account with filtered Gaussian white noise processes modeled with a modified Kanai‐Tajimi filter. Both the effectiveness of the optimization procedures and the resulting systems are evaluated through time history analyses with two sets of natural accelerograms corresponding to operating basis and safe shutdown earthquakes, respectively.